Numerical Analysis Study Of Sarawak Barrage River Bed Erosion And Scouring By Using Smooth Particle Hydrodynamic (SPH) - Mohd Khairun Nizar Mohd Tajudin, Mohd Khairun Nizar Mohd (Universiti Sains Malaysia, 2017)
Smooth Particle Hydrodynamic is the three-dimensional (3D) model. In this research work, three cases and one validation have been simulate using DualSPHysics. Study area of this research work was at Sarawak Barrage. The cases have different water level at the downstream. This study actually to simulate riverbed erosion and scouring properties by using multi-phases cases which use sand as sediment and water. The velocity and the scouring profile have been recorded as the result and shown in the result chapter. The result of the validation is acceptable where the scouring profile and the velocity were slightly different between laboratory experiment and simulation. Hence, it can be conclude that the simulation by using SPH can be used as the alternative to simulate the real cases.